Quality education management in Malaysia : an exploratory study / Rahmah Mohd Rashid and Shireen Haron - Mohd Rashid, Rahmah; Haron, Shireen (Universiti Teknologi MARA, Shah Alam, 2012)
This exploratory study examines Malaysian undergraduate students' perception on the effectiveness of their learning based on their evaluation of key factor areas concerning quality education management. Some 857 full time students enrolled in different faculty programs were randomly selected. Eight factors were examined to measure the students' perception, i.e., University Leadership, Strategic Planning, Students, Stakeholders and Market Focus, Measurement, Analysis and Knowledge Management, Faculty and Staff Focus, Process management, Organizational Performance Results, and Innovation. The students were asked to evaluate based on a five-point scale ratings, items concerning the eight factors in a questionnaire. Findings showed that the majority of respondents agreed moderately that the management exhibited acceptable quality in all the eight constructs. T-tests and ANOVA indicated significant difference in students' perception of all eight factors between the faculties and the Branch Campuses.